The role of social media in promoting entrepreneurship and innovation among youth in Saudi Arabia (A Field Study) - Al-Tamimi, Ahmad Abdrabuh (Journal of Economic, Administrative and Legal Sciences, 2025)
This study aimed to explore the role of social media in promoting entrepreneurship and innovation among youth in Saudi Arabia, focusing on the Riyadh region. A survey method was employed, combining interviews and questionnaires, with data collected from a sample of 109 entrepreneurs. The findings revealed that social media usage enhances innovation, marketing, and professional networking while reducing operational costs for entrepreneurial projects. The study also identified varying impacts of different platforms on product and service development. Based on these findings, the study provided recommendations to optimize social media utilization in fostering entrepreneurship and innovation in alignment with Saudi Vision 2030.